Characterization and optimization of a homemade ring dye laser. (1st February 2018) - Nanakar, H.
Highlights: The dye laser power versus the pumping laser power was determined. The effect of dye jet speed on the output laser power was also investigated. The optimum conditions for the laser operation have been determined. Abstract: Objectives: The characteristics of dye laser such as purity, concentration and dye solvent velocity have significant effects on the output power of laser. The main objective was to investigate the effects of the dye solvent velocity on the laser output power. Methods/Statistical analysis: A homemade ring dye laser (Rhodamine 6G) was used and the liquid dye was injected by a liquid jet and pumped by beam of a 6 W argon ion laser (λ = 488 nm). By using mechanical pumping, the liquid pressure was controlled and different velocities were selected. Findings: It was observed that by increasing the pressure, the output power of dye laser, was increased initially and then in a certain pressure variation region (0.65–0.69 MPa), some slight changes were detected. By increasing more dye liquid pressure, the laser output was decreased considerably. The maximum output laser power obtained in a wavelength ranges within 5702–6072 Å, was approximately 140 mW. It was seen that by increasing the pumping power, the dye laser output power was increased. Moreover, for each specific wavelength, there was a threshold power (in pumping laser) for dye laser emission in order to be initiated. For example for the laser emission at 5763 Å and 5990 Å, the minimum pumping laser powers are ~4.1 and 5.2 W, respectively. Dye solvent velocity in output power of dye laser is not appropriately discussed in previous studies, so it can be stated that in the current study, it was carried out with different conditions. Application/Improvements: Applying suitable dye solvent velocity is one of the important issues in designing ring dye laser that has been correctly discussed and utilized in the current study.